2013
DOI: 10.1186/cc12514
|View full text |Cite
|
Sign up to set email alerts
|

Stress hyperglycemia: an essential survival response!

Abstract: Stress hyperglycemia is common in critically ill patients and appears to be a marker of disease severity. Furthermore, both the admission as well as the mean glucose level during the hospital stay is strongly associated with patient outcomes. Clinicians, researchers and policy makers have assumed this association to be causal with the widespread adoption of protocols and programs for tight in-hospital glycemic control. However, a critical appraisal of the literature has demonstrated that attempts at tight glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
435
2
18

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 507 publications
(465 citation statements)
references
References 45 publications
10
435
2
18
Order By: Relevance
“…To, co se zdá, jako negativní účinek na funkci jednoho orgánu, může být z pohledu celého organismu prospěšně. Marik a Bellomo poukazují na možnost, že akutní hyperglykémie je mechanismem, jakým organismus také zvyšuje svoji šanci na přežití (97).…”
Section: Hyperglykémie U Kriticky Nemocných a Její Terapeutické Ovlivunclassified
“…To, co se zdá, jako negativní účinek na funkci jednoho orgánu, může být z pohledu celého organismu prospěšně. Marik a Bellomo poukazují na možnost, že akutní hyperglykémie je mechanismem, jakým organismus také zvyšuje svoji šanci na přežití (97).…”
Section: Hyperglykémie U Kriticky Nemocných a Její Terapeutické Ovlivunclassified
“…However, the blood glucose threshold above which stress hyperglycemia becomes harmful is unknown. Furthermore, we suggest that both the duration and the degree of hyperglycemia are important in determining whether hyperglycemia is protective or harmful [5]. It seems most unlikely that a few days of hyperglycemia would be harmful; indeed attempts at rapid correction of blood glucose in these patients may be harmful.…”
mentioning
confidence: 91%
“…Subsequent studies, the most important being the NICE-SUGAR study, demonstrated that intensive glucose control (81-108 mg/dl, 4.5-6.0 mol/l) increased mortality when compared to conventional glucose control (144-180 mg/ dl, 8.0-10.0 mmol/l) [4]. We have previously argued that hyperglycemia is a marker of illness severity rather than a cause of poor outcome [5]. Indeed, the degree of hyperglycemia is related to the degree of activation of the stress response.…”
mentioning
confidence: 99%
See 2 more Smart Citations